2023
DOI: 10.1002/adfm.202302191
|View full text |Cite
|
Sign up to set email alerts
|

Spin‐Phonon Scattering‐Induced Low Thermal Conductivity in a van der Waals Layered Ferromagnet Cr2Si2Te6

Abstract: Layered van der Waals (vdW) magnets are prominent playgrounds for developing magnetoelectric, magneto‐optic, and spintronic devices. In spintronics, particularly in spincaloritronic applications, low thermal conductivity (κ) is highly desired. Herein, by combining thermal transport measurements with density functional theory calculations, this study demonstrates low κ down to 1 W m−1 K−1 in a typical vdW ferromagnet Cr2Si2Te6. In the paramagnetic state, development of magnetic fluctuations way above Tc = 33 K … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 65 publications
(133 reference statements)
0
1
0
Order By: Relevance
“…Experimental studies have also reported on several 2D intrinsic magnetic materials, with some of them exhibiting semiconductor properties, including V(S/Se) 2 , 24,25 Cr(Cl/Br/I) 3 , 18,38–40 and Cr 2 (Ge/Si) 2 Te 6 . 41,42 However, the Curie temperatures of these currently available systems are usually quite low, which greatly limits their practical applications. It is worth noting that some systems have higher Curie temperatures, for example, the T C of 2H-VSe 2 is up to 300 K, but the origin of its magnetic order remains elusive both theoretically and experimentally.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental studies have also reported on several 2D intrinsic magnetic materials, with some of them exhibiting semiconductor properties, including V(S/Se) 2 , 24,25 Cr(Cl/Br/I) 3 , 18,38–40 and Cr 2 (Ge/Si) 2 Te 6 . 41,42 However, the Curie temperatures of these currently available systems are usually quite low, which greatly limits their practical applications. It is worth noting that some systems have higher Curie temperatures, for example, the T C of 2H-VSe 2 is up to 300 K, but the origin of its magnetic order remains elusive both theoretically and experimentally.…”
Section: Introductionmentioning
confidence: 99%